Basal Ganglia Traumatic Hematoma: Case Series and Literature Review - Pereira, Carlos Umberto; Kalkmann, Gabriela Ferreira; Nascimento, Isabela do Prado; Santos, Letícia Adrielle dos; Rabelo, Nicollas Nunes (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Introduction Basal ganglia traumatic hematoma (BGTH) is rare, occurring in 3% of closed traumatic brain injuries, and it is associated with a poor prognosis. In the present paper, the authors present a series of 16 BGTH cases, describing their causes, treatment, and results.Patients and Methods Thisis a retrospective study of 16 patients diagnosed with BGTH, associated with a literature review in the PubMed, ScienceDirect, and Google Scholar databases, using the terms craniocerebral trauma AND basal ganglia and basal ganglia AND hematoma AND trauma. Articles published in the period from 1986 to 2019 were selected, resulting in a total of 19 articles that met the inclusion criteria taking into account their citations and their respective impacts.Results Sixteen patients were studied. They were all male, with an average age of 21 years and 5 months. The main cause of BGTH was traffic accident (12). The mean score in the Glasgow coma scale at admission was 8. All patients underwent a computed tomography (CT) scan of the skull. The putamen was the most affected structure (5). Thirteen patients underwent conservative treatment, and three drained the associated intracranial hematoma. Nine patients died, and seven, and four had neurological sequel.Conclusions The neurosurgeon's knowledge of GBTH, including diagnosis and clinical surgical management, is extremely important, as this type of lesion is associated with a poor prognosis.
Keywords: basal ganglia; craniocerebral trauma; neuroimaging; traumatic cerebral hemorrhage